KONGSI KEMATIAN DAN PERUBAHAN RITUAL PROSESI KEMATIAN TIONGHOA DI PADANG - Erniwati, Eniwati; Syafrina, Yelda; Saumia, Zulfa (Paradigma: Jurnal Kajian Budaya, 2025)
This article discusses the changes in the implementation of death rituals organized by ethnic Chinese in Padang city. Documents in the form of photos and bylaws of the death ritual procession, an interview, and observations at the funeral home, crematorium of the Chinese socio-cultural and funeral association Himpunan Tjinta Teman (HTT), Himpunan Bersatu Teguh (HBT), and the Chinese cemetery complex in Bukit Sin Tiong and TPU Bungus Teluk Kabung are the sources of this article. The article's findings show that the performance of death procession rituals is an important part that marks the identity of the deceased and the family left behind. The ethnic Chinese of Padang still carry out death rituals in the Chinese tradition because there is a death congregation in the city of Padang that serves as a forum for preserving and organizing this ancestral tradition. In its development, the tradition of the death ritual procession has changed with the times, especially in the use of symbols, the stages of implementing a shorter and more efficient ritual process, the choice of the cremation process as a result of technological findings and the shift in ritual meaning from generation to generation of Chinese. These changes occurred in line with the changing times and the reforms adopted by the two Padang Chinese death societies as well as changes in the Chinese generation itself.